If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -3) + 2x = 89 Reorder the terms: 3(-3 + 4x) + 2x = 89 (-3 * 3 + 4x * 3) + 2x = 89 (-9 + 12x) + 2x = 89 Combine like terms: 12x + 2x = 14x -9 + 14x = 89 Solving -9 + 14x = 89 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 14x = 89 + 9 Combine like terms: -9 + 9 = 0 0 + 14x = 89 + 9 14x = 89 + 9 Combine like terms: 89 + 9 = 98 14x = 98 Divide each side by '14'. x = 7 Simplifying x = 7
| .25f+3=8 | | 3(4x+3)=68 | | 2(x+5)-10=8 | | 4x-20=7x+14 | | 15m-2(3+5m)= | | 15x^2-50y+35=0 | | 2-(8p-q)-7(p+6)+4q= | | -8x+x^2=-12 | | x^2-x-20=0 | | 7(p+3)=7b-4 | | f(11)=1/2(11)+5 | | 9(s+7)-(7s+m)-9m= | | f(11)=2(11)+5 | | 9(7x+8)+3(x+-10)= | | 7x+9=-11x+12 | | 7x+9and=-11x+12 | | -(9q+7)+3(2q-5)= | | 8y-2=14y-3 | | 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= |